REFLECTIONS ON NETWORKING DYNAMICS TO ADDRESS VIOLENCE AGAINST CHILDREN IN TANZANIA - Kamusiime, Annah; Sandi, Lydia Belinda; Kakuru, Doris (International Journal of Child, Youth and Family Studies, 2022)
This article is based on a study conducted to understand the functionality and connectivity of existing networks and their impact on the prevention and response to violence against children (VAC) in East Africa. We adopted an exploratory qualitative approach in which a bottom-up purposive selection of study participants was used. Data were collected using focus group discussions with grassroots actors, interviews with network leads at the grassroots district and national levels, and VAC network funders. The study was carried out in Tanzania’s Dar es Salaam region in three districts (Kigamboni, Temeke, and Ilala) and eight wards. Our findings show that because the nature of VAC is complex and multidimensional, efforts to respond to it also exhibit these qualities. Depending on the goal, networking takes various forms, and VAC networks can have unspecified lifespans. VAC networking results from strategic decision-making that yields many benefits, including a stronger voice and visibility, enhanced impact, and potential efficiency. However, networks also encounter bottlenecks that negatively impact their goals. This is an indication that VAC network actors ought to be more reflexive regarding the space they occupy in the network and intentionally pursue strong relationships among actors and networks.